Dovbnia N.P., Bondarenko L.M., Bobir D.V, Korenjuk R.A. Shock absorbers of woobling as alternative hydraulic. - Довбня, Н.П.; Бондаренко, Л.М.; Бобырь, Д.В.; Коренюк, Р.А. (Problems of Tribology, 2014)
As the shock absorbers in cars are mainly used hydraulic shock absorbers. It is believed that they are most appropriately determined by the rate of damping of vibrations. However, be aware that these shocks have at least two major drawbacks: first – complexity in manufacturing, requiring high production and high-skilled workers, and a second – difficulty pacing damping with dynamic change efforts.Because of these disadvantages of hydraulic shock absorbers logical to offer technologically easy to manufacture and easy to adjust the damping rate of the shock absorbers.Analysis of the results leads to the conclusion that the damping of oscillations in these cases, is close to the viscous resistance, so these shocks, when carrying out the necessary experimental investigations can be recommended as an alternative to hydraulic.